Decolonizing education in Latin America: critical environmental and intercultural education as an indigenous pluriversal alternative : critical environmental and intercultural education as an indigenous pluriversal alternative - Corbetta, Silvina (Taylor & Francis, 2023)
Tras defender la idea de que la Agenda 2030 consolida un modelo de “desarrollo” neoliberal hegemónico, analizamos cómo el ODS4 profundiza en una “educación para el desarrollo sostenible” utilitarista e instrumental. Alternativamente, se presentan las Epistemologías del Sur como modos de conocimiento que son capaces de alojar a una educación ambiental intercultural crítica (EAIC). Partiendo de una metodología cualitativa, se presentan dos extensos estudios etnográficos de caso, basados en entrevistas convivenciales, individuales y colectivas, con diferentes pueblos indígenas. Esta estrategia nos permite analizar dos casos diferentes de educación intercultural (una ‘que sí es’, y otra ‘que no es’) en América Latina: el modelo de educación intercultural bilingüe de las escuelas para qom en Rosario, y el modelo de educación autónoma de las escuelas zapatistas en Chiapas. Y mostramos cómo la experiencia de la “educación verdadera” zapatista nos permite mirar más allá del “desarrollo” y de la “escolarización”, allí donde la vida es urdimbre entre ecosistema(s) y cultura(s).

Following an argument that the 2030 Agenda consolidates a neoliberal hegemonic ‘development’ system, we analyze how SDG4 deepens an instrumental and utilitarian ‘education for sustainable development’. Alternatively, the Epistemologies of the South are presented as ways of knowing that are capable of accommodating a critical environmental and intercultural education (CEIE). Under a qualitative methodology, two extensive ethnographic studies were carried out, based on convivial individual and collective interviews with indigenous peoples. In addition, documentary analysis was carried out. This strategy made it possible to analyze two different cases of intercultural education (one of ‘that which is’ and the other of ‘that which is not’) in Latin America: the model of intercultural bilingual education of the schools for the qom in Rosario, and the autonomous education model of the Zapatista schools in Chiapas. We show how the experience of Zapatista’s ‘true education’ allows us to look beyond ‘development’ and ‘schooling’, to where life is a melding of ecosystem(s) and culture(s).
Keywords: Ciencias sociales::Geografía social y económica::Ciencias ambientales (aspectos sociales)